Visualizations of User Data in a Social Media Enhanced Web-based Environment in Higher Education - Silius, Kirsi; Tervakari, Anne-Maritta; Kailanto, Meri (International Journal of Emerging Technologies in Learning (iJET), 2013)
In this article, we introduce the results of a study concerning user data visualizations in the context of the TUT Circle, a social media enhanced web service for learning, networking, and communication at the Tampere University of Technology (TUT). Well-designed visualizations can provide valuable insight into student activity and participation in an online course, and therefore support both teachersâ?? and studentsâ?? strategic decision making. We found social network analytics and visualizations useful in providing information to improve the pedagogical practices of online courses, as well as the studentsâ?? overall engagement in their studies and study lives. However, to be useful, the visualizations need to have enough hints so that the users can interpret the different elements in them in the right way.